Effect of different protein levels of fry feed on the production of quality tilapia (Oreochromis niloticus) fry (Journal of the Bangladesh Agricultural University, 2012)
A 4-week long feeding experiment was conducted to evaluate the effect of different protein levels of quality Tilapia (O. niloticus) fry production in Agro-3 Fish Hatchery and Culture Farm, Boilor, Trishal, Mymensingh. Four days old 1247 fry (length 0.8 cm and weight 0.012 g) were stocked at the density of 1560/m2 in twelve synthetic hapas. Four   different treatments (T1, T2, T3 and T4) in three replications were used having different level of protein containing diets (T1,=35.95%, T2=40.43%, T3=45.61% and T4=50.85%) in the experiment. Feeds were supplied to fry at 4 h intervals during 24 h cycle upto satiation level. Sampling was done at 7 days interval throughout the experiment. The best growth was obtained at 35.95% protein level in T1 treatment. Therefore, a follow up second experiment with feeds having protein levels 30.12%, 33.42%, 36.19% and 39.01% encircling the best performed diet (35.95% protein) of the first experiment was conducted. Significantly (P